Effect of torrefaction on steam gasification of starchy food waste. (1st October 2019) - Huang, Jingchun; Qiao, Yu; Wei, Xianfeng; Zhou, Juntong; Yu, Yun; Xu, Minghou
Highlights: Gasification performance of the raw and torrefied starchy food wastes are compared. The cold gas efficiency of the raw sample is high even at low temperatures. The syngas from torrefied sample is more suitable for chemical synthesis. The torrefied sample shows better gasification performance at high temperatures. Abstract: This work compares the gasification of the raw and the torrefied leftover rice to understand the effect of torrefaction on steam gasification of starchy food waste at various temperatures. Torrefaction experiments were first performed at 240–300 °C to study the effect of torrefaction temperature on fuel properties of torrefied leftover rice. Then, gasification experiments of the raw and torrefied leftover rice sample were conducted in a fixed-bed reactor at 600–1000 °C and a steam/carbon (S/C) molar ratio of 2. It is found that the raw leftover rice can be completely converted into volatile products at 600 °C, but with a high tar yield of 20.4% and a low cold gas efficiency (CGE) of 60.5%. A further increase in gasification temperature to 700 °C greatly reduces the tar yield to 1.9% thus substantially increases the CGE to 94.9%. Further comparisons with the existing data from other feedstocks demonstrate that the raw leftover rice is a high-quality gasification feedstock which can achieve a high CGE at a low gasification temperature (i.e., 700 °C). In contrast, the gas yield of the torrefied leftover rice is low at low temperatures, but increases with gasification temperature due to enhanced char reforming reactions. This leads to the CGE of the torrefied leftover rice increasing from 16.7% at 600 °C to 91.1% at 1000 °C. It should be noted that the CGE of the torrefied leftover rice at 1000 °C is even higher than that of the raw leftover rice, due to increased coke formation from the raw leftover rice at high temperatures, most likely via the hydrogen abstraction and carbon addition reactions. While for the torrefied leftover rice, its coke formation is mainly attributed to the tar polymerization reactions. The results show that the gasification of torrefied leftover rice at high temperatures (>900 °C) generates high-quality syngas suitable for the synthesis of chemical products.